Desafios dos docentes não licenciados da área de recursos naturais do Instituto Federal do Amapá - NICACIO, Marcos Alves (Instituto Federal do Amapá, 2021)
The creation of federal institutes (FIs) in 2008 increased the number of professors working in the modality of professional and technological education. This expansion of the offer of vacancies has required the hiring of new teachers, teaching in integrated technical courses has been exercised by professionals from different areas of knowledge (bachelors and technologists). Some of them have never had contact with pedagogical training. The professional from bachelor's degrees and technologists, when faced with the classroom, does not usually have the teaching experience of licensed professionals, this lack of experience can bring numerous challenges to the teacher without pedagogical training. In view of this reality, the objective of the present study was to identify the main difficulties faced by non-licensed teachers who work in integrated high school courses of the natural resources area at the Federal Institute of Amapá. The study had a qualitative and quantitative approach, the data collection instrument used was the questionnaire. Twelve teachers participated in the research, 75% female and 25% male. The age of the participants ranged from 29 to 60 years, while academic education, 50% have a degree in agronomy and 50% in forestry. Only 25% of the teachers took specialization in the pedagogical area. All of the professors have graduate degrees at the master's level (100%) and 33.3% at the doctoral level, both in the undergraduate area. We realized that the greatest difficulties of teachers were linked to teaching and didactic methodologies. We conclude that it is not enough to only have mastery over the content, but also to know methodologies that favor learning. Authors suggest that continuing education supports teachers, enabling them to develop pedagogical knowledge and expand their teaching and learning capacities for teaching practice.